Enhanced redox activity of a hollow conjugated microporous polymer through the generation of carbonyl groups by carbonylative Sonogashira coupling. Issue 15 (28th March 2018) - Choi, Jaewon; Ko, Ju Hong; Kang, Chang Wan; Lee, Sang Moon; Kim, Hae Jin; Ko, Yoon-Joo; Yang, MinHo; Son, Seung Uk
Abstract : The carbonylative Sonogashira coupling reaction enhanced the redox activity of a hollow conjugated microporous polymer. Abstract : Redox active 1, 4-bis(3-phenylpropynoyl)benzene moieties were incorporated into a hollow conjugated microporous polymer via carbonylative Sonogashira coupling of 1, 3, 5-triethynylbenzene with 1, 4-diiodobenzene in the presence of carbon monoxide. The resultant redox active material showed enhanced energy storage performance for pseudocapacitors.